Biophysical insights into recombinant Zeocin binding protein: conformational stability and folding dynamics across pH and temperature - Alharbi, Sara; Malik, Ajamaluddin; Alamri, Abdulaziz; Khan, Javed Masood; Khan, Mohd. Shahnawaz; Alhomida, Abdullah; Ahmad, Tauseef (Frontiers in Molecular Biosciences, 2026)
Zeocin-binding protein (ZBP) confers resistance to the bleomycin family of antibiotics across a wide variety of prokaryotic and eukaryotic hosts. Zeocin is a bleomycin derivative used in cancer treatment. ZBP’s mechanism involves binding to Zeocin, shielding DNA from damage. In protein folding studies, ZBP, a versatile marker across various organisms, can be used to track protein folding by fusing it to target proteins in prokaryotes and eukaryotes. Despite its significance, ZBP’s biophysical properties are poorly studied. This study characterized the conformational changes, pH stability, solubility, and thermodynamic stability of recombinant ZBP from Streptoalloteichus hindustanus. ZBP’s aggregation tendency was assessed across pH ranges, showing notable changes near its isoelectric point (pI) of 4.5. Dynamic multimode spectroscopy analyzed ZBP’s thermodynamic properties at different pH levels, revealing distinct conformations and reversible thermal stress responses. At physiological and alkaline pH levels, ZBP undergoes a single reversible thermal transition between 60 °C and 80 °C with thermal transition midpoints (Tm) of 67.4 ± 0.1 °C and 65.4 ± 0.1 °C, respectively. However, at pH 2.0, the Tm was reduced to 54.3 ± 0.3 °C. Overall, this study characterized the biophysical stability of ZBP under various pH and thermal conditions, providing essential insights for its optimized application as a selectable marker in molecular biology.